Association between changes in self-esteem and smartphone dependency among Korean adolescents - Ah Jung Ko; Yu Shin Park; Jinhyun Kim; Eun-Cheol Park (PLoS ONE, 2025)
Increasing smartphone ownership across all age groups has raised concerns about the rising risk of smartphone addiction, particularly during adolescence when self-esteem development is critical. This study aimed to investigate the association between changes in self-esteem and smartphone dependency over a five-year period using data from the Korean Children and Youth Panel Survey (2018–2022). A total of 1,971 participants from the middle school 1st grade cohort were analyzed. Self-esteem was measured annually using the Rosenberg Self-Esteem Scale, with a cutoff of 25 points classifying individuals into high and low self-esteem groups. Self-esteem was measured annually, and year-to-year change variables were created by comparing each participant’s score to that of the previous year. These lagged changes were used to assess their association with smartphone dependency measured at the same time point: (1) good → good, (2) good → poor, (3) poor → good, and (4) poor → poor. Smartphone dependency was assessed using the Smartphone Addiction Proneness Scale, with measurements taken at each annual survey point. The Generalized Estimating Equations model was used to analyze the association between self-esteem changes and smartphone dependency. The results indicated that both males and females with consistently low self-esteem or those whose self-esteem declined were more likely to exhibit smartphone dependency compared to those with consistently high self-esteem (females: good → poor: adjusted odds ratio (OR) 2.19, 95% confidence interval (CI) 1.78–2.71; poor → poor: adjusted OR 2.21, 95% CI 1.81–2.70; males: good → poor: adjusted OR 2.09, 95% CI 1.76–2.50; poor → poor: adjusted OR 2.04, 95% CI 1.70–2.48). These findings emphasize that stable self-esteem during adolescence may reduce the risk of smartphone dependency and related health issues.